Gambaran Pengetahuan Lansia Tentang Gouty Artritis di Desa Tandengan Satu Wilayah Kerja Puskesmas Tandengan - Rivolta Alfiko Musak; Mutiara Sunrica Lomboan (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Gouty arthritis is a degenerative disease commonly found in the elderly due to aging and poor dietary habits. This study aims to describe the level of knowledge among elderly individuals regarding gouty arthritis in Tandengan Satu Village, under the working area of the Tandengan Health Center. The research employed a descriptive quantitative design with a purposive sampling technique, involving 165 elderly respondents. Data collection was conducted through structured questionnaires and analyzed using univariate analysis. The findings showed that the majority of respondents (52%) had a moderate level of knowledge, 26% had good knowledge, while 22% had poor knowledge. The results indicate that elderly knowledge regarding gouty arthritis in this area is still inadequate and requires improvement. Health education interventions tailored to the local cultural context are recommended to increase awareness and promote better disease management practices among the elderly population in rural settings.